2022
DOI: 10.1002/ecm.1518
|View full text |Cite
|
Sign up to set email alerts
|

Combined influence of food availability and agricultural intensification on a declining aerial insectivore

Abstract: Aerial insectivores show worldwide population declines coinciding with shifts in agricultural practices. Increasing reliance on certain agricultural practices is thought to have led to an overall reduction in insect abundance that negatively affects aerial insectivore fitness. The relationship between prey availability and the fitness of insectivores may thus vary with the extent of agricultural intensity.It is therefore imperative to quantify the strength and direction of these associations. Here we used data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 166 publications
(224 reference statements)
0
22
0
Order By: Relevance
“…Residual woodlots within these agro-intensive landscapes add to the tree lines separating fields to increase the length of "forest" edges, where insect abundance tends to be greatest (Boetzl et al, 2020;Evans et al, 2003;Jokimäki et al, 1998). The fledging success of Tree Swallows from the system presented here is greater in agro-intensive landscapes containing residual woodlots than in ones denuded of forest cover (Garrett et al, 2022a). It may therefore be hypothesized that the elevated insect abundance associated with these residual woodlots lead to greater provisioning rates and thus greater fledging success in this landscape context.…”
Section: Durationmentioning
confidence: 86%
See 4 more Smart Citations
“…Residual woodlots within these agro-intensive landscapes add to the tree lines separating fields to increase the length of "forest" edges, where insect abundance tends to be greatest (Boetzl et al, 2020;Evans et al, 2003;Jokimäki et al, 1998). The fledging success of Tree Swallows from the system presented here is greater in agro-intensive landscapes containing residual woodlots than in ones denuded of forest cover (Garrett et al, 2022a). It may therefore be hypothesized that the elevated insect abundance associated with these residual woodlots lead to greater provisioning rates and thus greater fledging success in this landscape context.…”
Section: Durationmentioning
confidence: 86%
“…Previous studies have indeed observed that agricultural intensification, including habitats impactful to insect communities and abundances, correlate with changes in dietary composition (Bellavance et al, 2018;English et al, 2017;Nocera et al, 2012), reductions in annual fitness proxies (Benton et al, 2002;Garrett et al, 2022a;Ghilain & Bélisle, 2008), and altered population growth (Stanton et al, 2018) of several aerial insectivore species. Studies linking prey availability to aerial insectivore breeding success have, however, often failed to observe such relationships (Dawson & Bortolotti, 2000;Dunn et al, 2011;Imlay et al, 2017;McClenaghan et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations